Perlindungan Hukum Terhadap Warisan Budaya Bawah Air(Underwater Cultural Heritage) Di Jalur Rempah:Evaluasi Pasca Undang-Undang Nomor 32 Tahun 2014 - Rayya Meishella Anjhani; Ibnu Cholid Ibrahim; Zakia Ramadina; Tio Prayoga (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The Spice Route, as a historic maritime corridor, not only reflects the dynamics of past global trade but also preserves an extraordinary wealth of underwater cultural heritage (UCH), consisting of thousands of shipwrecks and artifacts that are hundreds of years old. In this context, Law Number 32 of 2014 concerning Maritime Affairs was enacted as a legal instrument expected to provide comprehensive protection for UCH within Indonesian waters. Nevertheless, the effectiveness of the provisions contained in the law in ensuring the protection of UCH, particularly along the Spice Route, still requires critical juridical evaluation. This research aims to conduct an in-depth analysis of the legal framework governing the protection of UCH under Law Number 32 of 2014, while also identifying its normative weaknesses and the obstacles encountered in its implementation. The study employs a normative legal research method with a historical legal approach, in order to trace the evolution of regulatory frameworks and assess their relevance to contemporary needs in safeguarding UCH. The findings indicate that Law Number 32 of 2014 provides a general legal framework that has not yet been complemented by specific implementing regulations dedicated to UCH. Several juridical shortcomings are identified, including the absence of an operational definition of UCH, overlapping institutional authorities, disproportionate sanctioning mechanisms, and Indonesia’s failure to ratify the 2001 UNESCO Convention on the Protection of the Underwater Cultural Heritage. Based on these findings, this research recommends the urgent formulation of more specific and comprehensive implementing regulations, as well as the necessity for the Indonesian government to take progressive measures toward ratifying the 2001 UNESCO Convention, in order to strengthen the legal regime for the protection of UCH at both the national and international levels.